WOMEN'S FREEDOM OF EXPRESSION WITHIN THE FRAMEWORK OF DIGITAL CONSTITUTIONAL LAW: KEBEBASAN BERPENDAPAT PEREMPUAN DALAM BINGKAI HUKUM KONSTITUSI DIGITAL - Fatimah, Siti; Nuriyatman, Eko; MS, Nuruzzaman (Constitutional Law Society, 2025)
The digital transformation has reshaped the landscape of freedom of expression, creating new opportunities for participation while also exposing women to structural, normative, and cultural challenges. In Indonesia, although Article 28E of the 1945 Constitution guarantees these rights, the digital environment remains unsafe due to weak legal safeguards, gender-blind regulations, and entrenched patriarchal norms. Online gender-based violence or OGBV, including cyber harassment, doxing, and non-consensual image distribution, continues to silence women, while the misuse of the Electronic Information and Transactions (ITE) Law has frequently criminalized victims instead of providing protection. This article employs a normative-conceptual and comparative legal approach to assess these gaps. Case studies, such as the criminalization of women under the ITE Law, reveal how existing frameworks fail to address gender-specific vulnerabilities. A comparative perspective with the European Union’s General Data Protection Regulation (GDPR) and Australia’s Online Safety Act 2021 highlights best practices for safeguarding women’s digital rights through strong data protection and proactive victim-centered mechanisms. The study argues for gender-responsive digital constitutional reform in Indonesia, including legal clarification, enhanced digital literacy, strengthened data protection, and progressive constitutional interpretation. Such reforms are essential to transform formal guarantees into substantive protections and ensure that women’s freedom of expression is meaningfully realized in a democratic digital society. This article offers a unique contribution by integrating Indonesian case studies of women’s criminalization under the ITE Law with comparative perspectives from the EU’s GDPR and Australia’s Online Safety Act. Unlike existing literature that remains largely descriptive, this study provides a prescriptive-analytical framework for gender-responsive digital constitutional reform. It bridges constitutional law, digital rights, and gender justice, presenting concrete pathways to transform formal guarantees into substantive protections for women’s freedom of expression.